Penyelesaian Tindak pidana Ringan melalui Restorative Justice Conferencing Initiative - Noya, Ekberth Vallen; Walakutty, Ade (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Indonesia is a country that upholds the law, so Indonesia is called a country of law. This is clearly stated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, the formulation of which is